An Analysis on Reading of E-magazine by College Students - Garg, Dr. Pradeep Kumar; Arora, CMA (Dr.) Amit Kumar (The journal of contemporary issues in business and government, 2021)
E-magazine provides many oppportunies to readers that were not available before. The study attempted to determine the status of the reading of e-magazine in the college students. The study is based on the structured questionnaire which was analyzed with the help of pie charts and bar diagrams. For the study we consider only Ghaziabad region. The study found that urban area people more subscribed to e-magazine. More than half of the sample thinks that e- magazine is better than printed magazine and it will be preferred more by the people in future in compare to present time.